Effect Of PMMA And PVA Coating On The Performance Of Optical Microbottle Resonator Humidity Sensors - Md Johari, Md Ashadi; Jali, Mohd Hafiz; Pour, Meisam Parsa; Al Noman, Abdullah; Abdul Khudus, Muhammad Imran Mustafa; Maslinda, M. S.; Mohd Ali, Ummu Umairah (John Wiley and Sons Inc., 2020)
This article compares the performances of uncoated and coated optical microbottle resonators (MBR) for humidity sensing. A technique called “soften-and-compress” was used to form the MBR with midriff diameter of Db = 190 μm, stem diameter of Ds = 125 μm and bottle length of Lb = 182 μm. The MBRs were prepared in three different conditions, which are noncoated MBR, PMMA (poly methyl meth acrylate) coated MBR, and PVA (polyvinyl-alcohol) coated MBR. The MBRs characteristic was investigated by employing a 2 μm tapered microfiber and tested for humidity sensing within a humidity range of 40% to 95%. The Q-factor obtained were >104 for all MBRs. The performance as humidity sensor was defined by the sensitivity and linearity of MBRs, which were investigated based on wavelength shift and also the transmitted power. The MBRs are undergoing a 180-seconds stability test at 65% RH humidity level. It is found that the PVA coated MBR performed better than other MBRs as a humidity sensor based on sensitivity, linearity, and stability measurements.